PENGARUH PERFORMANCE EXPECTANCY, EFFORT EXPECTANCY, PERCEIVED SECURITY PADA SISTEM PEMBAYARAN ELEKTRONIK TERHADAP KESEJAHTERAAN JURU PARKIR - Axel Martien Atmojo; Nina Karina Karim (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2026)
This study aims to analyze the influence of performance expectancy, effort expectancy, and perceived security of the electronic payment system on the welfare of parking attendants in Mataram City. Employing an associative quantitative approach, this research collected primary data through a questionnaire distributed to 99 officially registered parking attendants in Mataram City. The study's population consists of active parking attendants registered with the Parking Attendant Information System (SIJUKIR), and a purposive sampling technique was used for sample selection. The collected data was then analyzed using multiple linear regression. The research findings indicate that the performance expectancy variable has a positive and significant influence on the welfare of parking attendants. Conversely, the effort expectancy and perceived security variables were found to have no significant relationship with the welfare of parking attendants. This study concludes that the perceived ease and benefits of technology use can improve welfare, but the factors of technological ease and security alone are insufficient if not supported by adequate external conditions.